# Evaluating $\lim_{x\to 0}\frac{\ln(1+x)-\ln(1-x)}{\arctan(1+x)-\arctan(1-x)}$ without differentiation

$$\lim_{x\to 0}\frac{\ln(1+x)-\ln(1-x)}{\arctan(1+x)-\arctan(1-x)}$$

So, I have this limit and I'm trying to solve this limit without differentiation.

I tried some steps, but they didn't come out well, and now I have no idea how to solve this. I know that the limit of $$\lim_{x\to 0}\frac{\arctan x }{x} = 1$$ but how is that going to help me in this case?

• Are you familiar with Taylor series? May 18, 2019 at 21:08
• @Monadologie What if you solve it without the Taylor series? Is that possible? Just by using limit properties? May 18, 2019 at 21:09
• @Monadologie If the OP doesn't want differentiation, I greatly doubt he wants Taylor series... May 18, 2019 at 21:09
• @wolly: You write that you've "tried some steps, but they didn't come out well". Please include those steps, even if they're wrong. This can help others avoid wasting time (theirs and yours) duplicating your effort and/or telling you things you already know; also, someone may be able to identify a simple flaw in your strategy (sign error or something).
– Blue
May 18, 2019 at 21:17
• @Blue Fine but you won't like what you will see(ibb.co/JQrpdL1) May 18, 2019 at 21:26

We will need the result $$\lim_{x\to0}\frac{\ln(1+x)}{x} = 1$$

With this, and the result given about the arctan limit, we can get our answer.

First, we have - \begin{align} \arctan(1+x)-\arctan(1-x)&=\arctan\left(\frac{(1+x)-(1-x)}{1+(1+x)(1-x)}\right)\\ &=\arctan\left(\frac{2x}{2-x^2}\right) \end{align}

So, \begin{align} \lim_{x\to 0}\frac{\ln(1+x)-\ln(1-x)}{\arctan(1+x)-\arctan(1-x)} &= \lim_{x\to 0}\frac{\ln\left(1+\frac{2x}{1-x}\right)}{\arctan\left(\frac{2x}{2-x^2}\right)}\\ &=\lim_{x\to 0}\left(\frac{\ln\left(1+\frac{2x}{1-x}\right)}{\frac{2x}{1-x}}\right)\lim_{x\to 0}\left(\frac{\frac{2x}{2-x^2}}{\arctan\left(\frac{2x}{2-x^2}\right)}\right)\lim_{x\to 0}\frac{\frac{2x}{1-x}}{\frac{2x}{2-x^2}}\\ &=1.1.\lim_{x\to 0}\frac{2-x^2}{1-x}\\ &=2 \end{align}

Hint:

$$\arctan p+\arctan q=\arctan\Bigl(\frac{p+q}{1-pq}\Bigr)\quad\text{if }pq<1.$$

Also, $$\;\ln(1+x)=x+o(x)$$, $$\;\ln(1-x)=-x+o(x)$$.

• How are ln(1+x)=x and ln(1-x)=-x? I know that ln(xy)=lnx+lny and ln(x/y)=lnx-lny. Is that what you used? May 18, 2019 at 21:29
• It's not equal to $x$ (or $-x$), but to $x$ with a complementary term very small w.r.t. $x$ (generically denoted $o(x)$). This is usually denoted as $\ln(1+x)\sim_{x\to 0} x$, in asymptotic analysis. May 18, 2019 at 21:34

You can use the known limit $$\lim_{x\to0}\frac{\ln(1+x)}{x}=1$$ Then you can rewrite your limit as $$\lim_{x\to0}\left(\frac{\ln(1+x)}{x}-\frac{\ln(1-x)}{x}\right) \frac{x}{\arctan(1+x)-\arctan(1-x)}$$ Since the part in parentheses has limit $$2$$, you can just compute the limit of the remaining fraction; better, of its reciprocal. With a similar trick $$\lim_{x\to0}\frac{\arctan(1+x)-\pi/4}{x}=\lim_{y\to\pi/4}\frac{y-\pi/4}{\tan y-1}= \lim_{z\to0}\frac{z}{\tan(z+\pi/4)-1}=\lim_{z\to0}\frac{z}{\tan z}\frac{1-\tan z}{2}=\frac{1}{2}$$ with the substitutions $$y=\arctan(1+x)$$ and $$y=z+\pi/4$$.

Can you finish?

All this needs is as $$c \to 0$$, $$\dfrac{\ln(1+c)}{c} \to 1$$ and $$\dfrac{\arctan(c)}{c} \to 1$$.

Since $$\ln(a)-\ln(b) =\ln(a/b)$$ and $$\arctan(a)-\arctan(b) =\arctan(\dfrac{a-b}{1+ab})$$,

$$\begin{array}\\ f(x) &=\dfrac{\ln(1+x)-\ln(1-x)}{\arctan(1+x)-\arctan(1-x)}\\ &=\dfrac{\ln(\frac{1+x}{1-x})}{\arctan(\frac{2x}{1+(1+x)(1-x)})}\\ &=\dfrac{\ln(\frac{1+x}{1-x})}{\arctan(\frac{2x}{2-x^2})}\\ \end{array}$$

Let $$\dfrac{1+x}{1-x} =1+c$$. Then $$1+x = (1+c)(1-x) =(1+c)-x(1+c)$$ so $$x(2+c) = c$$ or $$x =\dfrac{c}{2+c}$$.

Also,

$$\begin{array}\\ \dfrac{2x}{2-x^2} &=\dfrac{2\dfrac{c}{2+c}}{2-(\dfrac{c}{2+c})^2}\\ &=\dfrac{2c(2+c)}{2(2+c)^2-c^2}\\ &=\dfrac{2c(2+c)}{2(4+4c+c^2)-c^2}\\ &=\dfrac{2c(2+c)}{8+8c+c^2}\\ \end{array}$$

Then

$$\begin{array}\\ f(x) &=f(\dfrac{c}{2+c})\\ &=\dfrac{\ln(1+c)}{\arctan(\frac{2c(2+c)}{8+8c+c^2})}\\ &=\dfrac{\ln(1+c)}{\arctan(c\frac{4+2c}{8+8c+c^2})}\\ \end{array}$$

As $$c \to 0$$, $$\dfrac{\ln(1+c)}{c} \to 1$$ and $$\dfrac{\arctan(c\frac{4+2c}{8+8c+c^2})}{c} \to \dfrac{\arctan(\frac{c}{2})}{c} \to \dfrac12$$ so $$f(x) \to 2$$.

$$\lim_{u\to 0}\frac {u}{\tan u}=1.$$ So for $$|u|<\pi/2$$ let $$u=\arctan v.$$ Then $$1=\lim_{u\to 0}\frac { \arctan v}{v}=\lim_{v\to 0}\frac {\arctan v}{v}.$$

So $$\arctan v=vF(v)$$ where $$\lim_{v\to 0}F(v)=1.$$

From the angle-sum formulas of trigonometry, when $$x^2\ne 2$$ we have $$\arctan (1+x)-\arctan (1-x)=\arctan \frac {(1+x)-(1-x)}{1+(1+x)(1-x)}=$$ $$=\arctan \frac {2x}{2-x^2}=$$ $$=\frac {2x}{2-x^2}F(\frac {2x}{2-x^2}).$$

There are many ways to show that $$\log (1+x)=xG(x)$$ when $$|x|<1$$ where $$\lim_{x\to 0}G(x)=1.$$

For example for $$x\ge 0$$ we have $$x= \int_1^{1+x}(1)dt\ge \int_1^{1+x}(1/t)dt=\log (1+x)\ge \int_1^{1+x}(1+x)^{-1}dt=x(1+x)^{-1}$$ and there is a similar calculation for $$-1

So when $$|x|<1$$ we have $$\log (1+x)-\log (1-x)=xG(x)-(-xG(-x))=x(G(x)+G(-x)).$$

• $\cos (A-B)=\cos A \cos B+\sin A\sin B$ and $\sin (A-B)=\sin A\cos B-\sin B\cos A.$ So when none of $\cos A, \cos B, \cos (A-B)$ is $0$ we have $\tan (A-B)=(\tan A-\tan B)/(1+\tan A \tan B).$ So with $A=\arctan u$ and $B=\arctan v$ we have $\tan (\arctan u-\arctan v)=(u-v)/(1+uv).$ So $$\arctan u -\arctan v=\arctan ((u-v)/(1+uv)).$$ May 18, 2019 at 22:39